Intra‐tooth stable isotope analysis of dentine: A step toward addressing selective mortality in the reconstruction of life history in the archaeological record. Issue 2 (26th August 2014) - Sandberg, Paul A.; Sponheimer, Matt; Lee‐Thorp, Julia; Van Gerven, Dennis; Reitsema, Laurie J.; McIlvaine, Britney Kyle
ABSTRACT Intra‐tooth stable isotope analysis of dentine provides a more sensitive means to examine infant and childhood life history in the past than conventional cross‐sectional analyses that rely on age‐at‐death. In addition, reconstructions of early diet and life history using an intra‐tooth approach circumvent potential problems associated with mortality bias, which may operate strongly during infancy and childhood. We present new intra‐tooth stable carbon and nitrogen isotope profiles in dentine collagen of early forming permanent teeth in a sample of adults from the Medieval Nubian site of Kulubnarti. We interpret the profiles in terms of weaning behavior and dietary history, and we compare profiles generated from first molars and canines to explore the degree to which these tooth types correspond. We then compare the profiles to the occurrence of linear enamel hypoplasia to assess the relationship between the timing of the weaning process and stress events. Finally, we compare the longitudinal profiles to cross‐sectional stable isotope data obtained from rib collagen to investigate how life histories might differ between those that survived into adulthood and those that did not. Results suggest that canine and first molar profiles are in broad agreement, that hypoplastic stress events occurred during rather than before or after the weaning process in our sample, and that survivors appear to have weaned earlier than the average non‐survivor. We suggest that this approach may be useful for addressing the effects of selective mortality on reconstructions of early life history and the relationship between early life history and morbidity. Am J Phys Anthropol 155:281–293, 2014. © 2014 Wiley Periodicals, Inc.